A note on some epiphytic plants for their repellent activities against Tribolium castaneum adults - Chhabi, SB; Asaduzzaman, M; Das, S; Islam, N (University Journal of Zoology, Rajshahi University, 2010)
DOI: 10.3329/ujzru.v28i0.5293 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 77-80